TEACHER PROFESSIONALISM ON TEACHER PEDAGOGIC KNOWLEDGE IN MERAUKE – PAPUA - Rias Ning Astuti (STKIP Siliwangi, 2015)
English becomes an international language that has to be mastered by the students in Indonesia and many countries in the world. Teaching English is not easy as we thought. As an English teachers, we should master some criteria to be good teachers. Because English today in Indonesia is considered as a foreign language, then it difficult for the students to learn it. Teacher is also important in teaching learning process in the classroom, the foundation of English teacher education, teacher knowledge, and professionalism of the teacher is primary goal that should be mastered In this case, the writer tries to explore the phenomena that happened in Indonesia especially in East Indonesia, that is, Merauke - Papua. The educational system in Merauke- Papua is good enough, but there are several terms that should be changed by the government and the teachers themselves. There are some problems faced by the teacher when they teach in the class, such as: what they teach does not match with the skills the subject requires and they only focus on finishing the curriculum. In this context, the roles of the government is very important in order to improve the teacher professionalism in Indonesia, one of which is certification for the teacher and the government will increase their salary per month. But, it is not only the matter of salary, but the government should find another ways to improve the teacher’s professionalism such as: conference, seminars, or another activities.